(untitled) (VERUM: Journal of Scientific Initiation, 2024)
A common character throughout Brazil, the prayer woman is described in different ways, generally linked to the image of an elderly woman, capable of relieving the illness of the sick “clients” who seek her out. In this universe, speaking in the name of a religion, the prayer may not be understood if her religion is not considered. Through her work, as a popular scientist and member of a community, she creates a network of solidarity in which she and her clientele mainly figure. With this work, we aim to provide some reflections on commensality in the profession of prayer women. Even though the prayer woman identifies with a specific religion, the practice of her craft is sometimes confused with other knowledge coming from different religions or even other popular practices. This is an exploratory and descriptive study, with a qualitative approach. The study setting takes place in the municipality of Cuité-PB. The discourse analysis was carried out through the theoretical-conceptual studies of Fiorin (2008). In this context, reflecting on commensality in the gift relationships that are woven around prayer women can help us understand other perceptions of the world, as these actors are challenged to find alternatives and solutions for curing illnesses as new meanings and Meanings are produced within these relationships.